Pengaruh Brand Image, Customer Value, dan Service Quality terhadap Keputusan Pembelian (Studi pada Konsumen Pengguna Aplikasi Shopee di Masa Pandemi Covid-19) - Clara Vani Kurnia Sari (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2022)
The Covid-19 pandemic is able to change people's behavior in shopping, one of which is switching to a digital platform with various conveniences and benefits it receives. Shopee is a large e-commerce that is currently ranked first, but the proliferation of promotions from other e-commerce has certainly become a new competition for companies. The existence of this study aims to determine: (1) how the influence of brand image, customer value, and service quality variables partially on purchasing decisions, and (2) how the influence of brand image, customer value, and service quality variables simultaneously on purchasing decisions. This research uses quantitative methods. The population of this research is Shopee consumers who have made product purchase decisions on the Shopee application during the Covid-19 pandemic. The sample taken in this study were 120 respondents with a non-probability sampling method with a purposive sampling approach. The analytical method used is descriptive analysis, classical assumption test, and multiple linear regression, hypothesis testing with the help of SPSS 25. The results in this study indicate that brand image does not partially affect purchasing decisions, customer value and service quality partially influence decisions. purchasing, as well as brand image, customer value and service quality have a simultaneous effect on purchasing decisions.